Validation of a Mixed Reality-based Digital Book on the Topic of Algebra for Grade 7 - Andri Nugroho, Aryo; Dwijayanti, Ida; Prayito, Muhammad (KnE Social Sciences, 2024)
In the current era, learning has been touched by technology that develops very rapidly, one of which is the book metamorphosis from print to digital form. Therefore, we need a book in digital form which is called a digital book. Digital books will be more interesting if they can turn our environment into a digital space. One technology that can present digital objects in the real world and interact with them using touch is mixed reality. The purpose of the study is to produce a mixed reality-based digital book that is valid for improving students’ numeracy literacy skills. This study used Borg and Gall’s research and development pattern method. The data were collected through expert validation for product testing. In media validation, which includes general aspects such as aspects of learning presentation, aspects of language feasibility, and graphic aspects, the result meets the valid criteria with an average score of 5 validators of 92.8%. Material validation includes general aspects such as, aspects of material substance, learning aspects, and beneficial aspects, the result meets the valid criteria with an average score from 5 validators of 92.4%. Based on the results of media and material validation of the digital book, it can be concluded that it is suitable for use. The implication of this study is to make it easier for students to learn using digital books. Keywords: digital book, mixed reality, literacy, numeracy